1971
DOI: 10.1021/bi00794a025
|View full text |Cite
|
Sign up to set email alerts
|

Propanediol dehydratase system. Role of monovalent cations in binding of vitamin B12 coenzyme or its analogs to apoenzyme

Abstract: Holopropanediol dehydratase (EC 4.2.1.28) was resolved completely into the apoenzyme and corrinoid(s) upon gel filtration on a column of Sephadex G-25 in the absence of potassium ion. The apoprotein obtained by this resolution procedure could be reconstituted into the catalytically active holoenzyme by the incubation at 37' with added B12 coenzyme in the presence of potassium ion. The recovery of dehydratase activity was nearly quantitative. The major corrinoid recovered was identified as 5 '-deoxyadenosylcoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
76
1
3

Year Published

1973
1973
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 16 publications
10
76
1
3
Order By: Relevance
“…The most extensive studies of metabolism of I ,a-propanediol, mainly in Aerobacter aerogenes, were made by Abeles and co-workers. It was concluded that the dehydration of I ,a-propanediol to propionaldehyde appears to be an intramolecular oxidation-reduction reaction requiring vitamin BIZ coenzyme (Abeles & Lee, 1961) and that the coenzyme serves as hydrogen carrier (Brownstein & Abeles, 1961) in the dchydratase system that also involves monovalent cations (Toraya, Sugimoto, Tamao, Shimizu & Fukui, 1971). The object of our work was to study the metabolism of 1,2-propanediol in the rumen in greater detail, with particular emphasis on the end-products and upon the involvement of the metabolism of the diol in the economy of metabolic hydrogen in the rumen.…”
mentioning
confidence: 99%
“…The most extensive studies of metabolism of I ,a-propanediol, mainly in Aerobacter aerogenes, were made by Abeles and co-workers. It was concluded that the dehydration of I ,a-propanediol to propionaldehyde appears to be an intramolecular oxidation-reduction reaction requiring vitamin BIZ coenzyme (Abeles & Lee, 1961) and that the coenzyme serves as hydrogen carrier (Brownstein & Abeles, 1961) in the dchydratase system that also involves monovalent cations (Toraya, Sugimoto, Tamao, Shimizu & Fukui, 1971). The object of our work was to study the metabolism of 1,2-propanediol in the rumen in greater detail, with particular emphasis on the end-products and upon the involvement of the metabolism of the diol in the economy of metabolic hydrogen in the rumen.…”
mentioning
confidence: 99%
“…Specificity of hybrid enzymes for monovalent cations was determined by measuring the enzyme activity with 1,2-propanediol as substrate in the presence of monovalent cations (12). Figure 4 shows the relationship between ionic radius and relative cofactor activity of each metal ion.…”
Section: Characterization Of Hybrid Enzymesmentioning
confidence: 99%
“…Large and small components correspond to the ␣ 2 ␥ 2 complex and the ␤ subunit, respectively ( 6, 7 ). Their catalytic properties are similar, but they are different in the binding affinity for AdoCbl ( 8,9 ), substrate specificity ( 1-3, 10, 11 ), susceptibility to suicide inactivation by glycerol ( 2, 9, 10 ), monovalent cation specificity ( 1,11,12 ), and immunochemical reactivity toward anti-diol dehydratase antiserum ( 11 ) (for review, see Refs. 13-15 )).…”
mentioning
confidence: 99%
“…The molecular mechanism by which activating and inhibiting ions operate cannot be deduced from the experiments described above. It may, however, be supposed that, similarly to the activation of dioldehydratase [6][7][8], the cations act on the enzyme protein conformation thus altering the affinity for B12 or other cofactors and substrates.…”
Section: S-adenosylmethioninementioning
confidence: 99%
“…Though these ions only are able to exert relatively weak coordinative forces, the complex formation apparently enables them to keep enzyme proteins in specific biologically active conformations. Some B12-dependent enzymes have turned out to belong to this group of cation-sensitive enzymes [6][7][8][9][10][11][12]. Toraya et al [6][7][8] have shown that the active form of the deoxyadenosyl cobalamin-dependent propanediol dehydratase contains potassium ions which are supposed to facilitate the binding between enzyme and B12 coenzyme thus enhancing the enzymatic activity.…”
Section: Introductionmentioning
confidence: 99%